Pengaruh Media Pembelajaran Infografis Statis Terhadap Hasil Belajar Siswa dalam Mata Pelajaran Sejarah - Zulkifli, Mukaffi; Syaharuddin, Syaharuddin; Prawitasari, Melisa (Lambung Mangkurat University, 2024)
This research is motivated by problems in learning activities in History subjects, namely the lack of use of learning media amidst developments in technology and information. Learning media is something that is used to convey messages in the form of learning materials. An example of learning media that can be used is static infographic media. Static infographic media is media that synergizes data, text and images in the form of simple media aimed at readers. The use of text and images in static infographic media can make it easier for students to absorb the information contained in the media so that the use of static infographic media can influence student learning outcomes. The aim of this research is to determine the effect of using static infographic media on student learning result in the History subject class XI IPS at SMA Negeri 1 Martapura. In this research, quantitative method choosen as research method with Quasi Experiment model. Purposive sampling technique choosen as sampling technique in this research. The instruments used in this research are test instruments in the form of multiple choice questions to measure student learning results and non-test instruments in the form of student response questionnaires, media expert validation questionnaires and material expert validation questionnaires. The research results showed (1) the learning outcomes of experimental class students in the history of the Renaissance and Church Reformation subjects were higher than those of the control class, with an average score for the control class of 75.41 and the experimental class of 85.57. (2) based on data analysis of post-test values using the t-test, with the results of a significance value of Sig. (2-tailed) obtained is 0.000 < 0.050, meaning that Ha is accepted and Ho is rejected. This shows that there is an influence of the use of static infographic media on the learning outcomes of class XI IPS students. The conclusion from the research results is that there is an influence of the use of static infographic media on learning outcomes. This is shown by the difference in post-test scores for the experimental class and the control class. The post-test score in the experimental class was higher than the post-test score in the control class.